Influences of Environmental Conditions on the Cracking Tendency of Dry-Mixed Plastering Mortar - Ni Tongyuan; Yang Yang; Wu Dandan; Jiang Chenhui (Advances in Materials Science and Engineering)
Cracking tendency is one of the important performances of dry-mixed plastering mortar (DMPM). Environmental condition is a key factor to affect the cracking tendency of DMPM. For the purpose of evaluating the cracking resistance of DMPM and revealing the influence of environmental conditions on the cracking tendency of DMPM, a series of experiments were performed on restriction-induced cracking behaviors as well as free shrinkage, water loss, and mechanical properties of DMPM. The restricted shrinkage tests were based on ring tests and plate experiments. The results showed that the initial drying age exhibits significant influence on the cracking tendency of DMPM, and there was a stress balance period when the initial drying age was 2 days. But, the phenomena cannot be observed when the initial age was 3 d, 5 d, and 7 d. In order to eliminate the cracking tendency of DMPM, it should avoid water loss from the plaster layer during construction in practical engineering, especially, before initial drying ages.